Anti-alcoholism drug disulfiram inhibits PANoptosis by blocking mitochondrial permeabilization in macrophages - Li, Ya-ping; Niu, Xin-jian; Zhang, Ge; Chan, On-kei; Sun, Nuo; Hu, Bo; Shi, Zi-jian; Ouyang, Dong-yun; He, Xian-hui; Zha, Qing-bing (Frontiers in Immunology, 2025)
IntroductionPANoptosis is a form of inflammatory cell death that exhibits simultaneous activation of pyroptosis, apoptosis and necroptosis signaling. Disulfiram is a clinically used anti-alcoholism drug and can inhibit NLRP3 inflammasome activation and pyroptosis. However, it is unknown whether and how disulfiram interferes with PANoptosis and related inflammatory diseases.MethodsPANoptosis was induced in murine macrophages and related protein levels were assayed by immunoblotting. The effects of disulfiram on PANoptosis were assessed both in macrophages in vitro and in a mouse model of hemophagocytic lymphohistiocytosis (HLH) in vivo.ResultsMitochondrial permeabilization preceded lytic cell death upon PANoptosis and binding of GSDMD-NT, GSDME-NT and p-MLKL to mitochondria was linked to mitochondrial dysfunction, which was depending on cardiolipin synthesis in mitochondria. Intriguingly, disulfiram not only prevented mitochondrial permeabilization but also suppressed PANoptotic signaling activation in macrophages. Mechanistically, disulfiram prevented the binding of GSDMD-NT, GSDME-NT and p-MLKL from mitochondria to attenuate its permeabilization, release of its components and generation of reactive oxygen species. Furthermore, the assembly of PANoptosome was effectively blocked by disulfiram. In a mouse model of HLH, intraperitoneal administration of disulfiram substantially decreased systemic inflammation and mitigated liver, lung and kidney injury, which were accompanied by reduced activation of PANoptosis signaling in these organs.ConclusionA previously unappreciated action of disulfiram to inhibit PANoptosis both in vitro and in vivo was discovered, thus repurposing this anti-alcoholism drug for the treatment of PANoptosis-related inflammatory diseases.